A stick-slip omnidirectional powertrain for low-cost swarm robotics: Mechanism, calibration, and control - Klingner, John; Kanakia, Anshul; Farrow, Nicholas; Reishus, Dustin; Correll, Nikolaus (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2014)
We present an omnidirectional powertrain for swarm robotic platforms that relies on low-cost vibration motors.We describe a mechanism and controller to achieve full 3-DoF motion on the plane. The proposed approach does not require the motors to be in phase, and overcomes differences in manufacturing by a hardware-in-the-loop auto-calibration routine based on the Nelder-Mead algorithm, which issues motion commands via infrared and records the resulting trajectories using an off-the-shelf webcam. We show convergence results of the calibration routine and sample trajectories of the swarm robotic platform "Droplet" demonstrating turning and omnidirectional drive.